Okra mucilage as an encapsulating agent for magnesium hydroxide nano-capsules in oral drug delivery - Masoud Safari Yazd; Amirreza Shafieeha; Fatemeh Eslami; Leila Zargarzadeh (Scientific Reports)
Abstract The study investigates the utilization of okra mucilage as an encapsulating agent for the development of magnesium hydroxide nano-capsules for oral drug delivery systems. Given the advancements in drug delivery systems (DDSs) and the emerging interest in nanostructured drug delivery systems (NDDSs), the potential of okra mucilage for nanoencapsulation is explored. NDDSs hold promise for enhancing therapeutic efficacy while minimizing adverse effects. Okra mucilage is known for its biodegradability, non-toxicity, and cost-effectiveness, making it a suitable candidate for encapsulation processes. The sol–gel encapsulation method is employed to fabricate the encapsulated magnesium hydroxide particles (EMgPs). The EMgPs were characterized using XRD, FT-IR, Raman spectroscopy, and FESEM/EDS, confirming the successful encapsulation of magnesium hydroxide within the okra mucilage. The hydrophilic properties of the EMgPs were also assessed through contact angle measurements, revealing promising wettability for efficient drug release in the digestive system. Release tests in a simulated digestive system environment demonstrated a controlled and sustained release profile (zero-order release) of magnesium hydroxide from the EMgPs with a rate constant of 0.75 and 0.2894 mg mL−1 h−1 in gastric phase and intestinal phase, respectively. The findings highlight the potential of okra mucilage as an encapsulating agent in oral drug delivery systems and provide insights for further research in the field of nanomedicine.